PENGARUH BUDAYA ORGANISASI DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI PADA KANTOR BADAN PENDAPATAN DAERAH PROVINSI SULAWESI TENGGARA - Tamboko, Fiqih Saputra; Madjid, Rahmat; Juharsah, Juharsah; Panjaitan, Feliks Anggia BK; Ittaqullah, Nurul (Jurusan Manajemen, Fakultas Ekonomi dan Bisnis Universitas Halu Oleo, 2023)
This study aims to examine and explain the simultaneous and partial influence of organizational culture and work discipline on employee performance at the regional revenue agency office in Southeast Sulawesi province. This research approach is a survey with an explanotory research design. The sample of this study were 57 employees at the regional revenue agency office in Southeast Sulawesi province. The data collection method used a questionnaire. The analytical tool used is multiple linear regression. The results showed that organizational culture and work discipline had a positive and significant effect on employee performance at the regional revenue agency office in Southeast Sulawesi province, both simultaneously and partially. Thus it can be concluded that organizational culture and work discipline have a positive and significant contribution to improving employee performance as reflected in quantity, quality, time, service orientation, commitment, work initiatives and cooperation